Not My Daughter - Delinsky, Barbara (New York : Doubleday, 2010)
Devastated by her teenage daughter's pregnancy, single mother and high school principal Susan Tate is targeted by unfair criticism when the pregnancies of additional teens are rumored to be part of a pact.
Includes reading group guide.
Keywords: Mother-daughter relationship -- Fiction; Teenage pregnancy -- Fiction